Food Taboo on Mothers during Pregnancy in Aceh Tribe - Molina, Annisa (Indonesian Journal of Medical Anthropology, 2024)
Food taboo is a cultural prohibition on consuming certain types of food. The Aceh tribe is one of the tribes that still apply food taboos. Food taboos usually arise due to customs and beliefs that have been passed down from generation to generation, and are applied to pregnant women and nursing mothers. The negative impact of food taboos can result in the mother and foetus not being able to get good nutritional intake. Medical experts explain that pregnant women should eat healthy foods and should discuss with a doctor or nutritionist so that they can get the right advice.